Alimentação do peixe-voador Hirundichthys affinis (Gunther, 1866) no Atlântico Sudoeste Tropical - Dantas Neto, Abílio Bezerra (Brasil, 2017)
The study of species feeding helps in understanding aspects of their biology and population dynamics. The purpose of the present research was to analyze the food content, characterizing the feeding of the flying fish Hirundichthys affinis collected in two sites in the Atlantic Ocean Southwest Tropical. The surveys were carried out in July 2016 in the vicinity of the PIRATA Program buoy located in the western equatorial Atlantic, distant 323 nautical miles from the Areia Branca - RN, and in the slope off Macau – RN in January of 2017. Stomachs and guts contents were analyzed by the identified categories, regarding frequency and volumetric frequencies, which were combined in the calculation of Alimentary Index (IAi). The prey item volumes were ordered in NMDS and their significant differences tested by PERMANOVA, while the contribution of each food item to the differences between the sites was evaluated through the SIMPER analysis. However, morphometric, spatial and temporal factors influenced in a relevant way the diet of the species at each point, classifying H. affinis collected in the vicinity of the PIRATA float as carcinophagous and individuals caught off the coast of Macau as piscivorous tending to carcinophagous
Keywords: Índice Alimentar (IAi); Macau – RN; Boia PIRATA; Carcinófago; Alimentary Index (IAi); Macau - RN; Boia PIRATA; Carcinophagous; CIENCIAS BIOLOGICAS::ECOLOGIA